2018
DOI: 10.14716/ijtech.v9i8.2750
|View full text |Cite
|
Sign up to set email alerts
|

A Cause of Communication Failure in Managing Industrialized Building System (IBS) Projects: A Perspective View from Project Managers

Abstract: An effective communication process is an important element in distributing information to various project teams. The previous study demonstrates the importance of communication in the project management process in order to encourage project delivery processes successfully. Unfortunately, the issue of communication still dominates Industrialization Building System (IBS) because the project development process are still based on traditional methods. This research aims to explore the cause of communication challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Therefore, the organization must ensure that its staff is well-equipped with complete procedures and explicit directions to ensure that contact between team members runs smoothly. As for this review, 12 articles stated that procedure is one of the main difficulties affecting communication in the construction business (Nasirzadeh et al, 2020;Khoury, 2019;Akunyumu et al, 2019;Castillo et al, 2018;Kwofie et al, 2019;Eze et al, 2018;Pozin et al, 2018;Tran et al, 2017;Yap et al, 2017;Senaratne & Ruwanpura, 2016;Zulch, 2016;Chalker & Loosemore, 2016;Badi & Diamantidou, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the organization must ensure that its staff is well-equipped with complete procedures and explicit directions to ensure that contact between team members runs smoothly. As for this review, 12 articles stated that procedure is one of the main difficulties affecting communication in the construction business (Nasirzadeh et al, 2020;Khoury, 2019;Akunyumu et al, 2019;Castillo et al, 2018;Kwofie et al, 2019;Eze et al, 2018;Pozin et al, 2018;Tran et al, 2017;Yap et al, 2017;Senaratne & Ruwanpura, 2016;Zulch, 2016;Chalker & Loosemore, 2016;Badi & Diamantidou, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…This can be categorized into three main categories: physical communication barrier, emotional communication barrier, and language communication barrier. The articles that identified barrier as one of their communication problems in this review are (Nasirzadeh et al, 2020;Khoury, 2019;Akunyumu et al, 2019;Kwofie et al, 2019;Eze et al, 2018;Pozin et al, 2018;Yap et al, 2017;Al Mousli and El-Sayegh, 2016;Zulch, 2016;Chalker and Loosemore, 2016).…”
Section: Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Subramanian and others, [12], joining the research in the same way that Rahman and Gamil showed that communications presented several problems in projects: poor communication management, absence of a coordinated communications plan; lack of an efficient platform for communications, absence of institutional support and different levels of education within the work teams that required an appropriate communicative treatment. Now, Ahmad and others, [13], in their interest in analyzing the role of communication in project management conducted interviews with five project managers in order to evaluate the communication within them. The detected problems consisted of misunderstandings when spreading and analyzing information; absence of a communications plan that would guarantee the integration of the different phases of projects; communicative barriers due to the coexistence of diverse organizational cultures within the teams and the reluctance of high commands and managers to listen to the opinions and suggestions of employees of lower range.…”
Section: State Of Artmentioning
confidence: 99%
“…In:2 supports Haas and Fagerlund (2002). Coordination meetings are crucial for integration purposes; it is important that communication channels are established from the outset for IBS projects (Pozin et al, 2018). IBS construction can only start when design work is completed, unlike conventional projects.…”
Section: Initial Phasementioning
confidence: 99%